Consolidation of the perinatal care system and workload of obstetricians: an ecological study in Japan - Hattori, Sanae; Sakata, Nobuo; Ishimaru, Miho; Tamiya, Nanako (Frontiers in Global Women's Health, 2023)
Objectives: We examined the relationship between consolidation of delivery and workload of obstetricians working at perinatal centers. Methods: We conducted a descriptive analysis using perinatal care areas classified into three types (metropolitan, provincial, rural). We used the Herfindahl–Hirschman Index (HHI) as an index of consolidation, proportion of deliveries at clinics as an indicator of low-risk deliveries, and deliveries per center obstetrician as an indicator of obstetricians' workload. We used >150 deliveries yearly as an excess indicator. The correlation between the HHI and obstetricians' workload and the proportion of deliveries at clinics was examined using Pearson’s correlation coefficient. Results: The proportion of areas with >150 deliveries yearly was higher in consolidated areas. In provincial areas, obstetricians' workload was positively correlated with the HHI and was negatively correlated with the proportion of deliveries at clinics. Conclusions: Obstetricians' workload may be increasing in areas with higher consolidation. In provincial areas, center obstetricians’ workload could be reduced not only by consolidation but also by sharing the role of handling low-risk deliveries with clinics and hospitals with obstetric units other than perinatal centers.